Lycium barbarum (Wolfberry) Increases Retinal Ganglion Cell Survival and Affects both Microglia/Macrophage Polarization and Autophagy after Rat Partial Optic Nerve Transection. Issue 5 (May 2019) - Li, Hong-Ying; Huang, Mi; Luo, Qiu-Yan; Hong, Xi; Ramakrishna, Seeram; So, Kwok-Fai
The rat partial optic nerve transection (PONT) model has been used for studying secondary degeneration of retinal ganglion cells (RGCs) in recent years. In this study, we carried out PONT of the temporal side of rat optic nerves, whereas PONT was carried out of the superior side in the previous publication. We found that this surgery is better and easier than the previous method and can produce a repeatable and reliable model. We detected significant changes in the polarization of microglia/macrophages and the level of autophagy in optic nerves after PONT. We also used this model to detect the effects of the polysaccharides extracted from Lycium barbarum (LBP) on the survival of RGCs and the changes in the polarization of microglia/macrophages and the level of autophagy after PONT. We find that LBP can delay secondary degeneration of RGCs after temporal injury of optic nerves, promote the M2 polarization of microglia/macrophages, and down-regulate the level of autophagy after PONT. In conclusion, we find that the polarization of microglia/macrophages and the autophagy level change after PONT; LBP treatment delays secondary degeneration of RGCs; and the polarization of microglia/macrophages and the level of autophagy are also altered after LBP treatment.